2012
DOI: 10.1371/journal.pone.0034406
|View full text |Cite
|
Sign up to set email alerts
|

Extract of Pleurotus pulmonarius Suppresses Liver Cancer Development and Progression through Inhibition of VEGF-Induced PI3K/AKT Signaling Pathway

Abstract: Liver cancer or hepatocellular carcinoma is one of the leading causes of cancer-related deaths. Conventional chemotherapies are limited by the development of drug resistance and various side effects. Because of its non-toxicity and potent biopharmacological activity, metabolites derived from mushrooms have received more attention in cancer therapy. Our previous studies have demonstrated the anticancer effects of polysaccharide-protein complexes derived from the Pleurotus mushrooms. The aim of this study was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 63 publications
0
38
0
Order By: Relevance
“…This study provided evidence that erinacine facilitated the opening of MPTP and induced the apoptosis of HCC HepG2 cells in a dose-dependent manner, in In this study, we demonstrated that the PI3K/Akt-GSK-3β signaling pathway was activated in HCC tissues and cells, and that treatment with erinacine and LY294002 resulted in the inhibition of this pathway. A consistent study revealed that the extract of Pleurotus pulmonarius (an edible mushroom) inhibited the proliferation and invasion of HCC in vitro and in vivo through the suppression of the PI3K/Akt signaling pathway [29]. Moreover, the PI3K/ Akt/mTOR pathway was found to be activated in HCC and enhance invasion and metastasis through the up-regulation of the metalloproteinase-9 matrix in HCC [30].…”
Section: Discussionmentioning
confidence: 97%
“…This study provided evidence that erinacine facilitated the opening of MPTP and induced the apoptosis of HCC HepG2 cells in a dose-dependent manner, in In this study, we demonstrated that the PI3K/Akt-GSK-3β signaling pathway was activated in HCC tissues and cells, and that treatment with erinacine and LY294002 resulted in the inhibition of this pathway. A consistent study revealed that the extract of Pleurotus pulmonarius (an edible mushroom) inhibited the proliferation and invasion of HCC in vitro and in vivo through the suppression of the PI3K/Akt signaling pathway [29]. Moreover, the PI3K/ Akt/mTOR pathway was found to be activated in HCC and enhance invasion and metastasis through the up-regulation of the metalloproteinase-9 matrix in HCC [30].…”
Section: Discussionmentioning
confidence: 97%
“…Akt in HCC can be usually activated by all kinds of tumor growth-promoting factors (such as PDGF and Angs), and result in increasing the generation of NF-КB, which can induce the expression of Bcl-2, Bcl-XL and Survivin to inhibit the activity of Caspase-3 and Caspase-7, and also promote the expression of XIAP to restrain the effects of Caspase-3/7/9 and finally antagonize the apoptosis-inducing effects of drugs (Hoesel et al, 2013;Kang et al, 2011;Lau et al, 2009;Xu et al, 2012). In this research, the potential interventions of SLBZP may exert through decreasing NF-КB, Bcl-2, Bcl-XL, Survivin and XIAP, and directly/indirectly increasing Caspase-3/9.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor growth is enhanced by a variety of growth promoters including PDGF, VEGF and angiogenins (Romano, 2013;Hoesel et al, 2013;Kang et al, 2011;Linkous et al, 2012;Xu et al, 2012;Lau et al, 2009). They do so by activating Akt and NF-КB signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have suggested that, in HCC, PP reduces the expression of secretory VEGF, which in turn mediates autocrine regulation of PI3K/Akt signaling in xenograft BALB/c nude mice. PP can also enhance sensitivity to the chemotherapeutic drug cisplatin (68).…”
Section: Sources Of Polysaccharides Targeting Growth Factors In Hccmentioning
confidence: 99%